2007
DOI: 10.1103/physrevb.76.064430
|View full text |Cite
|
Sign up to set email alerts
|

Heisenberg antiferromagnet with anisotropic exchange on the kagomé lattice: Description of the magnetic properties of volborthite

Abstract: We study the properties of the Heisenberg antiferromagnet with spatially anisotropic nearest-neighbor exchange couplings on the kagomé net, i.e., with coupling J in one lattice direction and couplings JЈ along the other two directions. For J / JЈ տ 1, this model is believed to describe the magnetic properties of the mineral volborthite. In the classical limit, it exhibits two kinds of ground state: a ferrimagnetic state for J / JЈ Ͻ 1/2 and a large manifold of canted spin states for J / JЈ Ͼ 1 / 2. To include … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 36 publications
2
47
1
Order By: Relevance
“…37, on the other hand, used a large-N expansion applied to the Sp͑N͒-symmetric generalization of the model. In the limit JЈ Ӷ J, they found that the chains are completely decoupled, and the interstitial spins show some ͑short-range͒ spin-spin correlation that is compatible with a spiral ordering pattern.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37, on the other hand, used a large-N expansion applied to the Sp͑N͒-symmetric generalization of the model. In the limit JЈ Ӷ J, they found that the chains are completely decoupled, and the interstitial spins show some ͑short-range͒ spin-spin correlation that is compatible with a spiral ordering pattern.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Examples include large-N expansions of the Sp͑N͒-symmetric generalization of the model, 36,37 a blockspin perturbation approach to the trimerized kagome lattice, 37 spin. 37,38 Our approach is complementary to these studies in that it offers a fairly controlled analysis of the quasi-onedimensional limit using powerful field-theoretical methods [39][40][41] that have originally been developed for the investigation of quantum critical systems in one dimension. Recently, the quasi-one-dimensional version of the kagome antiferromagnet in a strong magnetic field, assuming that the intermediate spins are fully polarized, has been studied using similar techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The subsets of this model which have been treated semiclassically or quantum mechanically are J 1 = J 1 > 0, J 2 = 0, and D z = 0, the isotropic kagome DM model (IKDM) 7,8,18 and J 1 = J 1 > 0, J 2 = 0, and D z = 0, the anisotropic kagome (AK) model. 5,6 In addition, recent L(S)DA + U calculations have suggested a model where −J 1 /J 1 ∼ 1.2-2, −J 2 /J 1 = 1.1-1.6, and J 1 = 8.6 meV. This model, which we call the coupled chain (CC) model, has only been treated classically so far.…”
Section: S(q)mentioning
confidence: 99%
“…12 Over the years, Volborthite has also inspired several theoretical studies. [13][14][15][16][17] In this work, we investigate possible quantum spin liquid and magnetically ordered phases on the distorted Kagome lattice, in view of the spatially anisotropic spin exchange model proposed earlier by the density functional theory (DFT) computations. 18 The distorted Kagome lattice corresponding to the so-called J − J − J 1 − J 2 model represents the nonsymmorphic layer space group, p2gg, that possesses glide symmetry, the combination of reflection and a fractional translation.…”
Section: Introductionmentioning
confidence: 99%